Targeting Cell-Specific Molecular Mechanisms of Innate Immunity in Atherosclerosis - Sauter, M.; Langer, H. F. (Frontiers in Physiology, 2022)
Mechanisms of innate immunity contribute to inflammation, one of the major underlying causes of atherogenesis and progression of atherosclerotic vessel disease. How immune cells exactly contribute to atherosclerosis and interact with molecules of cholesterol homeostasis is still a matter of intense research. Recent evidence has proposed a potential role of previously underappreciated cell types in this chronic disease including platelets and dendritic cells (DCs). The pathophysiology of atherosclerosis is studied in models with dysfunctional lipid homeostasis and several druggable molecular targets are derived from these models. Specific therapeutic approaches focussing on these immune mechanisms, however, have not been successfully introduced into everyday clinical practice, yet. This review highlights molecular insights into immune processes related to atherosclerosis and potential future translational approaches targeting these molecular mechanisms.